Selective dialysis-based extraction of succinic acid using phosphonium ionic liquids: A hybrid membrane-IL approach for sustainable downstream processing - Quijada-Maldonado, E; Zurob-Guzman, E (TAYLOR & FRANCIS INC, 2026)
The downstream recovery of bio-based succinic acid (SA) from fermentation broths remains a critical challenge due to the presence of interfering compounds such as microorganisms, substrates, and coproducts. In this study, we developed a hybrid separation system combining selective dialysis through a cellulose acetate membrane with a hydrophobic phosphonium-based ionic liquid (P6,6,6,14[PHOS]) as the receiving phase. This approach was evaluated using a model Yarrowia lipolytica fermentation broth, and its performance was compared against an aqueous glucose phase under laminar flow conditions. Although the glucose phase exhibited a slightly higher SA flux (1.42 vs. 1.24 kg<middle dot>m-2 <middle dot>h-1), the ionic liquid system demonstrated exceptional selectivity: 300 for SA/glycerol and 500 for SA/water, making it hundreds of times more selective than the glucose system. Integration of the membrane reduced ionic liquid losses, prevented contamination of the fermentation broth, and stabilized the separation interface, enabling consistent and sustainable performance. Mass transfer analysis revealed that the IL phase contributed 99% of the overall resistance, primarily due to the hydrophilic character of the membrane. These results underscore the potential of hydrophobic phosphonium ILs in membrane-based selective extraction, offering an efficient and environmentally friendly strategy for bio-based succinic acid recovery